DAYA TERIMA, KADAR PROTEIN DAN SERAT FISH CRACKERS DENGAN PENAMBAHAN TEPUNG KACANG HIJAU (Vigna radiata): Acceptance, Protein Content, and Fiber Content of Fish Crackers with the Addition of Mung Bean Flour (Vigna radiata) - Zakaria; Asikin, Hijrah; Mas’ud, Hikmawati; Hajirah (Media Gizi Pangan, 2024)
The production of crackers is still predominantly based on cereals from grains, resulting in relatively low protein content. Fish crackers, on the other hand, are processed foods that already contain animal protein based on previous research, but consumer panels have indicated that the aroma is still considered unpleasant. Therefore, the addition of a food ingredient containing plant protein that can neutralize the aroma is necessary. One such source of plant protein rich in fiber that can neutralize the aroma is mung bean flour. This study aims to determine the acceptance, protein, and fiber content of fish crackers with the addition of mung bean flour (Vigna radiata). This study employed a pre-experimental design with a one-shot case study design, utilizing three treatment formulas with mung bean flour ratios of 40% (F1), 50% (F2), and 60% (F3), with a standard formula without the addition of mung bean flour as the control (F0). The results showed that the addition of mung bean flour could affect the acceptance of fish crackers based on aroma (p=0.017) and taste (p=0.000), while color (p=0.131) and texture (p=0.435) were not significantly affected. The selected formula based on the accumulation of panelist preference acceptance percentages of 92-96% was Formula 1 (with 40% mung bean flour addition), which had a protein content of 16.63% and fiber content of 26.96%.